Odpowiedzi

2010-01-13T14:02:03+01:00
2(x³-2x²+1)-(3x³+4x²+2x-1) = 2x³ - 4x² + 2 - 3x³ - 4x² - 2x + 1 = -x³ -8x² - 2x + 3
(x²-4x²)(2x-1)-(x³+x²-x-2) = 2x³ - x² - 8x³ + 4x² - x³ -x² + x + 2 = -7x³ + 2x² + x + 2
(2x-3)²+(3x-1)(3x+1)= 4x² + 9 + 9x + 3x - 3x - 1 = 4x² + 9 + 9x
(x+3)³ = x³ + 6x + 9
(x-2)(x+2)-(2x+5)² = x² + 2x - 2x - 4 + 4x² - 25 = 5x²- 29
Najlepsza Odpowiedź!
2010-01-13T14:04:43+01:00
2(x³-2x²+1)-(3x³+4x²+2x-1)=2x³-4x²+2-3x³-4x²-2x+1=-9x²-2x+3
(x²-4x²)(2x-1)-(x³+x²-x-2)=2x³-x²-8x³+4x²-x³-x²+x+2=-7x³+2x²+x+2
(2x-3)²+(3x-1)(3x+1)=4x²-12x+9+9x²-1=13x²-12x+9
(x+3)³=x²+6x+9
(x-2)(x+2)-(2x+5)²=x²-4-(4x²+20x+25)=x²-4-4x²-20x-25=-3x²-20x-29
daj najlepsze:)
ta vienia czy gienia ma zle:P
2010-01-13T14:06:18+01:00
2(x³-2x²+1)-(3x³+4x²+2x-1)=2x³-4x²+2-3x³-4x²-2x+1=-x³-8x²-2x+3

(x²-4x²)(2x-1)-(x³+x²-x-2)=2x³-8x³-x²+4x²-x³-x²+x+2=-7x³+2x²+x+2

(2x-3)²+(3x-1)(3x+1)=4x²-12x+9+9x²-1=13x²-12x+8

(x+3)³=(x+3)(x²+6x+9)=x³+3x²+6x²+18x+9x+27=x³+9x²+27x+27

(x-2)(x+2)-(2x+5)² =x²-4-4x²-20x-25=-3x²-20x-29